IDENTIFICATION OF SUBSURFACE STRUCTURES IN LANDSLIDE AREAS IN BRAND DISTRICT - Fadhilah, Nurul; Kadri, Muhammad; Tampubolom, Togi (EINSTEIN (e-Journal), 2025)
A research has been conducted on the identification of subsurface structure of landslide area using geoelectric and geomagnetic methods in Pangambatan Village, Merek District, Karo Regency. The research aims to determine the subsurface structure, causes of landslides and indicators of landslides. Geo-electrical measurements were taken using ARES-G4 v4.7 (Automatic Resistivity System) and GPS (Global Position System) with three passes. Each track has a total of 16 electrodes with a distance of 5 meters for each electrode. The geomagnetic method uses a PPM (Proton Procession Magnetometer) type GSM-19T. Data collection with the number of points obtained 25 measuring points. The results showed that the subsurface structure using geoelectricity contained alluvium, sand, gravel, silt, groundwater, sandstone, limestone and andesite rock types. The resistivity value of the first track ranges from 500-2000 Ωm, the second track is 50-4,500 Ωm, and the third track is 200-1,500 Ωm. Based on geomagnetic research, there are rock types with susceptibility values of sandstone (0.0010; 0.0015) cgs, limestone (0.0030) cgs and clay (0.0020) cgs. The causes of landslides in the research location are sand, gravel, alluvium and clay as landslide-carrying materials, while sandstone and limestone as sliding planes. Soil indicators that cause landslides based on geoelectric results are the second track with a difference of two layers of contrasting resistivity values. And geomagnet results with low susceptibility values.